E-waste management: towards an appropriate policy - Askari, Arameh; Ghadimzadeh, Azadeh; Gomes, Chandima; Ishak, Mohd Bakri (International Institute for Science, Technology & Education, 2014)
The socio-environmental impact of rapidly increasing piles of electrical and electronic waste or E-waste at global level has been evaluated in detail. Malaysian scenario was selected as a case study to analyse various issues regarding generation, storage, transportation and disposal of E-waste. Generation of E-waste has been estimated to be about 652909 tonnes in 2006 and was extrapolated to reach around 706 000 tonnes in 2011 and about 1.2 million tonnes in 2020 in Malaysia alone. E-waste basically includes disposed materials of refrigerators, calculators, alarm clocks, computers, printers, televisions, monitors, audio setups, electronic thermometers, laser printer, etc, most of which contain batteries and other components. They carry traces of heavy elements and toxic compounds that threaten human and animal health and various other parts of ecosystem. As per the estimation, over 75% of subjects interviewed in this study has lack of knowledge in storage and disposal techniques of E-waste. The situation may be worse in some other parts of the world. Finally, this paper proposes viable procedures for the safe management of E-waste.